Radio Drama Revisited: Laila Aboulela’s The Museum and The Sea Warrior - Ebtesam Elshokrofy (Beni-Suef University International Journal of Humanities and Social Sciences, 2023)
Radio drama belongs to the wider term ‘audio literature’ — a genre that mixes both literary and intermedial studies. Radio drama has been underestimated and unappreciated all over its history on four grounds: rarity, invisibility, audience negativity and “secondariness”. The aim of this paper is to defend radio drama against these accusations proving that radio drama has its own merits and thus, its success should be judged only upon its ability to convey to the ear whatever appeals to the eye, and its ability to give the listeners the same sense of a full- length stage play.Theoretically, radio drama manages to translate such senses via the use of four overlapping elements: descriptive dialogue, sound effects, narration, and character.Two radio plays by the Sudanese writer Laila Aboulela are chosen to argue the research point. They are The Museum and The Sea Warrior. Keywords: Audio literature, Laila Aboulela, Radio drama, Sound effects, The Museum, The Sea Warrior.